2013
DOI: 10.1016/j.ajpath.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Overload Induces Visceral Adipose Tissue Insulin Resistance

Abstract: Increased iron stores associated with elevated levels of the iron hormone hepcidin are a frequent feature of the metabolic syndrome. The aim of this study was to assess the effect of dietary iron supplementation on insulin resistance and the role of hepcidin in C57Bl/6 male mice fed a standard or iron-enriched diet for 16 weeks. Iron supplementation increased hepatic iron and serum hepcidin fivefold and led to a 40% increase in fasting glucose due to insulin resistance, as confirmed by the insulin tolerance te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
127
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 38 publications
16
127
2
3
Order By: Relevance
“…These results suggest that iron accumulates in adipose tissue in humans with increased body fatness and impaired insulin action [15], as previously demonstrated in mice [12][13][14].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results suggest that iron accumulates in adipose tissue in humans with increased body fatness and impaired insulin action [15], as previously demonstrated in mice [12][13][14].…”
Section: Introductionsupporting
confidence: 83%
“…A previous study using the 3T3-L1 mouse cell line suggested the importance of iron-related genes in adipocyte physiology [11]. Interestingly, recent studies in mice revealed that an iron-enriched diet induced iron accumulation and insulin resistance in visceral adipose tissue (VAT) [12] and that adipocyte iron overload reduced adiponectin biosynthesis in parallel with induction of insulin resistance [13]. Another recent study in mice showed impaired macrophage iron handling in the setting of obesity-associated adipose tissue dysfunction, which resulted in adipocyte iron uptake and overload [14].…”
Section: Introductionmentioning
confidence: 99%
“…This ironenriched diet was associated at the same time with visceral adipose tissue hyperplasia and hypertrophy (45). An iron-restricted diet led to the opposite results, with low amounts of circulating free fatty acids and triglycerides (46).…”
Section: Iron Affects Adipocyte Differentiation and Adipose Tissue Hymentioning
confidence: 97%
“…Altered adipose tissue biology and dysregulation of adipokine synthesis may promote liver injury by increased insulin resistance and also by other direct and indirect effects on hepatic and adipose tissue lipid metabolism 8. Studies in animals and tissue culture models have demonstrated an iron‐induced dysregulation of the synthesis of three adipokines with such roles, namely adiponectin, leptin, and resistin 9, 10, 11…”
mentioning
confidence: 99%
“…More recently, it has been demonstrated that iron down‐regulates the appetite‐suppressing hormone leptin in mice fed a high iron diet through iron‐dependent activation of cyclic adenosine monophosphate responsive element‐binding protein 10. Two other adipokines, resistin and retinol binding protein‐4 (RBP‐4), have been associated with insulin resistance,8 and iron has been proposed as a regulator of serum concentrations of both these hormones 11, 12. Tumor necrosis factor α (TNFα) and interleukin‐6 (IL‐6) are cytokines secreted from adipose tissue as adipokines as well as from other tissues 8.…”
mentioning
confidence: 99%